What if? 2 : additional serious scientific answers to absurd hypothetical questions - Munroe, Randall (Houghton Mifflin Harcourt, 2014)
"The #1 New York Times-bestselling author of What If? and How To provides his best answers yet to the weirdest questions you never thought to ask The millions of people around the world who read and loved What If? still have questions, and those questions are getting stranger. Thank goodness xkcd creator Randall Munroe is here to help. Planning to ride a fire pole from the moon back to Earth? The hardest part is sticking the landing. Hoping to cool the atmosphere by opening everyone's freezer door at the same time? Maybe it's time for a brief introduction to thermodynamics. Want to know what would happen if you rode a helicopter blade, built a billion-story building, made a lava lamp out of lava, or jumped on a geyser as it erupted? Okay, if you insist. Before you go on a cosmic road trip, feed the residents of New York City to a T. rex, or fill every church with bananas, be sure to consult this practical guide for impractical ideas. Unfazed by absurdity, Randall consults the latest research on everything from swing-set physics to airplane-catapult design to clearly and concisely answer his readers' questions. As he consistently demonstrates, you can learn a lot from examining how the world might work in very specific extreme circumstances. Filled with bonkers science, boundless curiosity, and Randall's signature stick-figure comics, What If? 2 is sure to be another instant classic adored by inquisitive readers of all ages"--